The effect of organisational absorptive capacity on business intelligence systems efficiency and organisational efficiency. Issue 2 (5th November 2020) - Al-Eisawi, Dalia; Serrano, Alan; Koulouri, Theodora
Abstract : Purpose: Business intelligence (BI) systems (i.e. technology and procedures that transform raw data into useful information for managers to enable them to make better and faster decisions) have enormous potential to improve organisational efficiency. However, given the high expenditure involved in the deployment of these systems, the factors that will enable their successful integration should be thoroughly considered and assessed before these systems are adopted. Absorptive capacity (ACAP) is the ability of organisations to gather, absorb and strategically influence new external information, and as such, there is a strong theoretical connection between ACAP and BI systems. This research aims to empirically investigate the relationship between the dimensions underpinning ACAP (i.e. acquisition, assimilation, transformation and exploitation) and whether and how they affect the efficiency of BI systems, which, in turn, can enhance organisational efficiency. Design/methodology/approach: This study formulates five hypotheses addressing the effect of ACAP dimensions on BI systems efficiency and the effect of BI systems efficiency on organisational efficiency. It synthesises previous qualitative work and current research to derive sets of measures for each of the key constructs of the study. It follows a quantitative methodology, which involves the collection of survey data from senior managers in the telecommunications industry and the analysis of the data using partial least squares – structural equation modelling (PLS-SEM). Findings: The results of the analysis confirmed the validity of the constructs and proposed measures and supported all five hypotheses suggesting a strong positive relationship between the ACAP dimensions, acquisition, assimilation, transformation and exploitation and the efficiency of BI systems and a strong effect of BI systems efficiency on organisational efficiency. Practical implications: The study offers a comprehensive model of ACAP and BI systems efficiency. The set of measures that underpin these constructs could help researchers understand how ACAP dimensions are practically implemented and could contribute to their efforts to develop ACAP measurement instruments. At the same time, the model can help managers assess the readiness of their firms to adopt BI systems and identify which areas should be further developed, before committing to the substantial financial investment associated with BI systems. It also provides a set of practical solutions that could be implemented to enable a more robust ACAP and support a better integration of BI systems. Originality/value: Following an empirical approach, this study refines one's theoretical and practical understanding of ACAP as an organisational dynamic capability and its dimensions; it provides an account on how each dimension affects different aspects of BI systems efficiency, which, in turn, may contribute to the improvement of organisational efficiency. Moreover, the study reframes ACAP measures as a set of requirements that can be practically assessed and followed before attempting to purchase BI systems.